Carbon Dioxide Emissions Intensity Convergence: Evidence From Central American Countries - Apergis, Nicholas; Payne, James E.; Rayos-Velazquez, Marco (Frontiers in Energy Research, 2020)
This paper extends the literature on the convergence of carbon dioxide emissions intensity and its determinants (energy intensity and the carbonization index) for six Central American countries over the period 1971 to 2014. Using the Phillips-Sul club convergence approach, the results indicate two distinct convergence clubs with respect to carbon dioxide emissions intensity and energy intensity. The carbonization index yields a single convergence club with Panama exhibiting non-convergent behavior. In light of the results, policies oriented toward the continued investment in renewable energy sources, clean energy technology, improved energy efficiency, restoration of forests, and movement toward carbon neutrality are desired goals to mitigate the environmental pressures associated with carbon dioxide emissions as a component of greenhouse gases.